2001
DOI: 10.1046/j.1365-2141.2001.02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T‐lymphocyte antigen‐4 microsatellite polymorphism is associated with multiple myeloma

Abstract: Summary. Multiple myeloma (MM) is a B-lineage malignancy with unknown aetiology. It has been considered that predisposing genetic factors might be implicated in the disease. In this study, the microsatellite polymorphism in the exon 3 of the cytotoxic T-lymphocyte antigen-4 (CTLA-4) gene was analysed in patients with MM and monoclonal gammopathy of undetermined significance (MGUS), together with ethnically matched healthy controls.The results showed that frequencies of the genotype 86/86 and of the allele 86 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 12 publications
(13 reference statements)
4
41
0
Order By: Relevance
“…A reduced inhibitory function of CTLA-4 has been suggested for the (AT) n polymorphisms. Alleles with long repeat regions have been associated with Grave's disease, myasthenia gravis, and multiple myeloma and have been correlated with a decrease in the CTLA-4 inhibitory function in myasthenia gravis [6,19,20]. In agreement with previous reports on allelic frequencies of the CTLA-4 (AT) n polymorphism in Caucasian populations [12,21], we found a high frequency of the short allele (AT) 8 in NHL patients and controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A reduced inhibitory function of CTLA-4 has been suggested for the (AT) n polymorphisms. Alleles with long repeat regions have been associated with Grave's disease, myasthenia gravis, and multiple myeloma and have been correlated with a decrease in the CTLA-4 inhibitory function in myasthenia gravis [6,19,20]. In agreement with previous reports on allelic frequencies of the CTLA-4 (AT) n polymorphism in Caucasian populations [12,21], we found a high frequency of the short allele (AT) 8 in NHL patients and controls.…”
Section: Discussionsupporting
confidence: 91%
“…Polymorphisms in the CTLA-4 gene have been associated with several autoimmune diseases, including blood disorders. Recent reports suggest that CTLA-4 polymorphisms represent a susceptibility locus for multiple myeloma and monoclonal gammopathies of undetermined significance and may contribute to the pathogenesis of autoimmune hemolytic anemia [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies supported a role for aberrant class switch recombination early in the natural history of the disease group suggesting that factors both in genetic and the environment may interact with this mechanism (6). Recent studies revealed that the genetic predisposing factors involved in microsatellite polymorphism (7), single nucleotide polymorphism (SNP) (8,9), methylation (10), mutation as well as deletion (11). Various cytokines such as IL-6, TNF-α, IL-1β and immune regulatory molecules like CTLA-4 (cytotoxic T-lymphocyte antigen-4) as well as proto-oncogene such as p53, p16, nuclear factor IκB, etc., are reported to be the predisposing factors (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…319,322,323 Significant associations have been reported for 3 IjBa polymorphisms, 324 genetic variants of nonhomologous end joining DNA ligase IV 325 and the microsatellite polymorphism CTLA-4. 326 These findings need to be corroborated in larger studies. Evidence for associations with other polymorphisms is limited, but no significant associations have been reported for methionine synthase A2756G, 327 methylenetetrahydrofolate reductase C677T or A1298C, 327,328 glutathione S-transferase l1 and u1, 329 BCL10, 330 or the endostatin gene polymorphism D104N.…”
mentioning
confidence: 95%